Scalable quantum computation with cavity QED systems - Giovannetti, V; Vitali, D; Tombesi, P; Ekert, A (American Inst of Physics, 2000)
A scheme for implementing quantum logic operations within a cavity of QED configuration is presented. This scheme is particularly suitable for the direct implementation of some useful many-qubit quantum gates. From a general point of view, the scheme is analogous to the linear ion trap scheme, except that the high-Q cavities play the role of the ions, and the atoms play the role of the quantum bus.